2007
DOI: 10.1016/j.ijsu.2006.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium slope predicts hypocalcaemia following thyroid surgery

Abstract: Serum calcium slope may be useful in identifying patients suitable for early discharge following thyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 8 publications
2
14
0
2
Order By: Relevance
“…As previously reported by Edafe et al, we found no difference between preoperative serum calcium levels in PoSH patients compared to controls. Furthermore, our results showed that PoSH patients had a sharper fall in serum calcium levels than controls after operation, which is in accordance with the results published by Walsh et al (20). Regarding preoperative PTH levels, correlative to the results of Brophy et al, we found no difference between patients with PoSH and controls (21).…”
Section: Discussionsupporting
confidence: 93%
“…As previously reported by Edafe et al, we found no difference between preoperative serum calcium levels in PoSH patients compared to controls. Furthermore, our results showed that PoSH patients had a sharper fall in serum calcium levels than controls after operation, which is in accordance with the results published by Walsh et al (20). Regarding preoperative PTH levels, correlative to the results of Brophy et al, we found no difference between patients with PoSH and controls (21).…”
Section: Discussionsupporting
confidence: 93%
“…Su mayor vascularización es una dificultad añadida para la localización y preservación de las paratiroides 4,13 , si bien no todas las series son coincidentes con estos hallazgos 14 . Esta mayor incidencia de hipocalcemia postoperatoria en pacientes con Graves-Basedow, sobre todo en las mujeres, puede ser debida a la influencia de las hormonas tiroideas sobre el metabolismo del calcio y el hueso, ya que actúan acelerando la creación y la remodelación ósea 11 .…”
Section: Discussionunclassified
“…Autotransplantation of parathyroid tissue after frozen-section confirmation is utilized if there is any concern of devitalization, and it is associated with a decreased risk of permanent hypoparathyroidism (192,193). Postoperatively, several approaches can predict which patients are at an increased risk of developing hypocalcemia, including serial measurements of serum calcium (194) as well as measurement of a peri-operative intact parathyroid hormone (iPTH) level. The utility of postoperative iPTH is fairly well established with a level of <10-15 pg/mL correlating with an increased risk to develop clinically significant hypocalcemia (195,196).…”
Section: Recommendation Rating: a And Recommendation 12(d)mentioning
confidence: 99%